Clinical and immunological features of the atopic dermatitis in children - E. B. Belan; M. A. Chueva; T. L. Sadchicova (Аллергология и Иммунология в Педиатрии)
Background: “atopic march” (AM) is the natural history of allergy mostly in children.   The aim: to describe the production of biomarkers of allergic inflammation in dependence on the duration of AD.   Patients and methods. 94 children suffered from atopic dermatitis (AD) have been included to the study. The severity of the disease has been estimated, serum level of total IgE, IL- 4, interferon gamma and sIL- 2R have been estimated.   Results. Coexistence of AR and AD was diagnosed in 32/94 (34.0 %) patients. Less severity of AD (SCORAD 32.3 ± 9.17 score vs 22.2 ± 2.29 score, p < 0.05), but higher serum level of total IgE (Ме 123 [Q1- Q3 67–156] IU/ml vs Ме 53 [Q1- Q3 5–108] IU/ml, р < 0.001), IL- 4 (Ме 12.0 [Q1- Q3 8.7–16.1] pg/ml vs Me 6.0 [Q1- Q3 2.2–12.1] pg/ml, р = 0.04) and sIL- 2R (Ме 2.1 [Q1- Q3 0–20] IU/ml vs Me 0 [Q1- Q3 0–12.9] IU/ml, р = 0.34) are detected in comorbid patients. Eposides of wheezing are associated with additional risk of AD (OR 2.3 [95 % CI 1, 18–4,54]).   Discussion. The development of AR in children with AD is considered as progression of natural history of allergy. In our study it was associated with higher level of IgE, IL- 4 and sIL- 2R. At the same time the comorbid patients had less severity of AD.   Conclusion. The coexistence of AD and AR in 3- year-old children is associated with less severity of skin symptoms but higher frequency of sensitization to inhalant allergens than in AD. AM is accompanied by higher production of Th2- dependent parameters and markers of early activation of T- cells. The probability of the AM is higher in 2 times if there were wheezing episodes in the anamnesis.